2014
DOI: 10.1530/eje-14-0249
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative octreotide treatment of acromegaly: long-term results of a randomised controlled trial

Abstract: Objective: Randomised studies have demonstrated a beneficial effect of pre-surgical treatment with somatostatin analogues (SSA) in acromegaly when evaluated early postoperatively. The objective of this study was to evaluate the long-term surgical cure rates. Methods: Newly diagnosed patients were randomised to direct surgery (nZ30) or 6-month pretreatment with octreotide LAR (nZ32). The patients were evaluated 1 and 5 years postoperatively. Cure was defined as normal IGF1 levels and by normal IGF1 level combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…Acromegaly is an uncommon hormonal condition that develops most commonly from benign somatotroph pituitary adenomas; the clinical indications connected with acromegaly are a result of the chronic overproduction of growth hormone (GH) and insulin-like growth factor 1 [1,2]. Systemic complications usually connected with the chronic hypersecretion of GH and insulin-like growth factor 1 (IGF-1) include acromegaly, soft tissue changes, and arthralgia, and comorbidities include type 2 diabetes, hypertension, carpal tunnel syndrome, and sleep apnea [3].…”
Section: Introductionmentioning
confidence: 99%
“…Acromegaly is an uncommon hormonal condition that develops most commonly from benign somatotroph pituitary adenomas; the clinical indications connected with acromegaly are a result of the chronic overproduction of growth hormone (GH) and insulin-like growth factor 1 [1,2]. Systemic complications usually connected with the chronic hypersecretion of GH and insulin-like growth factor 1 (IGF-1) include acromegaly, soft tissue changes, and arthralgia, and comorbidities include type 2 diabetes, hypertension, carpal tunnel syndrome, and sleep apnea [3].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term observational data (1 and 5 years post-operatively) for these patients, however, revealed no significant impact of pre-operative treatment on macroadenomas (Fougner et al 2014). Remission rates (IGF-1 ≤ age-adjusted ULN) of 49 and 18% were found in a single-centre study of 98 patients with newly diagnosed macroadenomas who received 4-month pre-treatment with lanreotide Autogel before surgery or surgery without pre-treatment, respectively ).…”
Section: Clinical Utility As First-line Therapymentioning
confidence: 81%
“…The value of primary therapy (pre-surgical administration) is controversial, but a recent meta-analysis by Fougner et al suggested a trend favoring preoperative SSA treatment [16]. However, one third of patients responded poorly or was resistant to SSA [25].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the octreotide suppression test (OST) has become routine practice in many endocrine centers [12], but the value of the OST in predicting long-term response to SSA therapy is still controversial [12][13][14][15]. Moreover, shortterm pre-surgical treatment with SSA in macroadenomas has been supported by a few studies and a recent meta-analysis [16], but it is unclear whether or not the OST can predict the efficacy of SSA after a relatively shorter period of usage, e.g. 3 months.…”
Section: Abbreviated Parameters and Formulasmentioning
confidence: 99%